2020
DOI: 10.1007/s00134-020-06266-1
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic haemostatic assay augmented protocols for major trauma haemorrhage (ITACTIC): a randomized, controlled trial

Abstract: Purpose: Contemporary trauma resuscitation prioritizes control of bleeding and uses major haemorrhage protocols (MHPs) to prevent and treat coagulopathy. We aimed to determine whether augmenting MHPs with Viscoelastic Haemostatic Assays (VHA) would improve outcomes compared to Conventional Coagulation Tests (CCTs). Methods: This was a multi-centre, randomized controlled trial comparing outcomes in trauma patients who received empiric MHPs, augmented by either VHA or CCT-guided interventions. Primary outcome wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
223
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(242 citation statements)
references
References 31 publications
5
223
0
2
Order By: Relevance
“…This trial demonstrated no statistical evidence that the use of VETs versus standard therapy guided by standard coagulation tests improved 28 day mortality. However, similar confounding factors were also found with the PROPPR trial [ 99 ]. Despite the high injury severity scores, a relatively small percentage of either group received MT within 24 h. This is also reflected by the low incidence of TIC in both groups.…”
Section: Vet-guided Goal-directed Resuscitationsupporting
confidence: 67%
See 4 more Smart Citations
“…This trial demonstrated no statistical evidence that the use of VETs versus standard therapy guided by standard coagulation tests improved 28 day mortality. However, similar confounding factors were also found with the PROPPR trial [ 99 ]. Despite the high injury severity scores, a relatively small percentage of either group received MT within 24 h. This is also reflected by the low incidence of TIC in both groups.…”
Section: Vet-guided Goal-directed Resuscitationsupporting
confidence: 67%
“…Additionally, the authors of the trial do not comment on the percentage of centers which used either ROTEM or TEG devices to guide BCT. They state: “The [VET] used at each study site was determined by existing familiarity with a specific device appliance and to ensure a balanced use of the devices across the study” [ 99 ]. This is of importance due to the heterogeneity of thresholds for administering BCT [ 100 , 101 ].…”
Section: Vet-guided Goal-directed Resuscitationmentioning
confidence: 99%
See 3 more Smart Citations